Literature Review: Personalised Medicine Tools for Antidepressant Management - Parshenkov, Mikhail A; Dyakonova, Anna N; Skovorodko, Polina P; Rodionova, Galina M (Scripta Medica, 2025)
Antidepressants are widely used in clinical practice, including for conditions beyond major depression (MD) disorders. However, clinicians still lack reliable tools to match patients with the right drug. Many individuals either fail to respond to the first prescribed agent or discontinue treatment due to side effects. This review focuses on two promising solutions: therapeutic drug monitoring (TDM) and pharmacogenetic testing. TDM measures the actual drug concentration in blood, rather than the prescribed dose. It's important to keep in mind that some individuals exhibit rapid or slow drug metabolism, leading to side effects or no effect at all. For example, for antidepressants like escitalopram, venlafaxine and paroxetine, blood levels often explain treatment response better than dose alone. Pharmacogenetics adds another layer, showing how genetic differences, especially in CYP2C19 and CYP2D6 – can change how drugs are processed. Other gene variants, like those in ABCB1 or SLC6A4, affect how well the drug gets into the brain or how patients tolerate it. Taken together, TDM and pharmacogenetics shift antidepressant prescribing from guesswork to evidence-based decision-making. By measuring drug levels and accounting for genetic variability, clinicians can better match each patient with the right treatment: earlier and with greater confidence. This approach improves efficacy, minimises adverse effects and reduces unnecessary switching or prolonged suffering. As prescribing expands, often beyond psychiatric indications and into long-term use without follow-up – the need for precision grows. What was once an aspirational model of care is becoming a clinical streamline in modern pharmacology.
Keywords: Drug monitoring; Pharmacogenetics; Antidepressive agents; Depressive disorder, major; Monoamine hypothesis; Precision medicine